2022
DOI: 10.1002/wps.21010
|View full text |Cite
|
Sign up to set email alerts
|

Use of low‐dose quetiapine increases the risk of major adverse cardiovascular events: results from a nationwide active comparator‐controlled cohort study

Abstract: At standard doses used for schizophrenia or bipolar disorder, quetiapine has been associated with weight gain and increased levels of triglycerides, to tal cholesterol and lowdensity lipoprotein (LDL) cholesterol, which are risk factors for cardiovascular morbidity and mortality. However, this drug is also commonly used offlabel at low doses for anxiolytic or hypnotic purposes, and its cardiovascular safety at these doses is unknown. We aimed to assess the risk of major adverse cardiovascular events with use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…We thank Prof. Østergaard and Dr. Rohde for their comments on our cohort study investigating the association between use of low-dose quetiapine and major adverse cardiovascular events recently published in World Psychiatry (Højlund et al, 2022a). The authors express their concerns on three issues: i) that the finding of an increased risk of major adverse cardiovascular events is due to residual confounding, ii) that this finding is interpreted as being causal, and iii) that an increased risk of cardiovascular events is not weighted against a potential beneficial effect from off-label use of quetiapine in low doses.…”
Section: To the Editormentioning
confidence: 99%
“…We thank Prof. Østergaard and Dr. Rohde for their comments on our cohort study investigating the association between use of low-dose quetiapine and major adverse cardiovascular events recently published in World Psychiatry (Højlund et al, 2022a). The authors express their concerns on three issues: i) that the finding of an increased risk of major adverse cardiovascular events is due to residual confounding, ii) that this finding is interpreted as being causal, and iii) that an increased risk of cardiovascular events is not weighted against a potential beneficial effect from off-label use of quetiapine in low doses.…”
Section: To the Editormentioning
confidence: 99%
“…7 Recently, low-dose quetiapine use has been associated with an increased risk of major adverse cardiovascular events, defined as nonfatal myocardial infarction, nonfatal ischemic stroke, or death from any cardiovascular causes. 8 However, it is currently not known whether low doses of quetiapine are also associated with an increased risk of hyperglycemia or dyslipidemia. As quetiapine is frequently used off-label in low doses, 2,[9][10][11][12] this question is of particular public health interest and concern.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia and dyslipidemia that have been associated with quetiapine use at higher doses 3,7 are important risk factors for cardiovascular disease 7 . Recently, low‐dose quetiapine use has been associated with an increased risk of major adverse cardiovascular events, defined as nonfatal myocardial infarction, nonfatal ischemic stroke, or death from any cardiovascular causes 8 . However, it is currently not known whether low doses of quetiapine are also associated with an increased risk of hyperglycemia or dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…We read the recent article by Højlund et al, entitled "Use of low-dose quetiapine increases the risk of major adverse cardiovascular events: results from a nationwide active comparator-controlled cohort study" (Højlund et al, 2022) with interest. In this observational study based on data from Danish nationwide registers, the authors compare the rate of major adverse cardiovascular events (as defined by non-fatal myocardial infarction or ischaemic stroke, or death from cardiovascular causes) among patients receiving low-dose quetiapine to that of patients using the Z-drug hypnotics zopiclone (imovane/imozop) or zolpidem (ambien/stilnoct), while adjusting for potential confounding using propensity score weights based on 100 covariates.…”
mentioning
confidence: 99%
“…The authors "found an increased risk of major adverse cardiovascular events with low-dose quetiapine, one of the most frequent uses of any individual antipsychotic medication, compared to use of Z-drugs." (Højlund et al, 2022), which led them to conclude that "On the basis of these findings, we suggest that use of off-label low-dose quetiapine for sedative or hypnotic purposes should be discouraged" (Højlund et al, 2022). Being familiar with the Danish registers and the inherent limitations of studies based on these data sources, we find this conclusion, as well as the causal statement in the title of the article ("Use of low-dose quetiapine increases the risk of major adverse cardiovascular events : : : " (Højlund et al, 2022)), to be problematic for the following reasons:…”
mentioning
confidence: 99%